BIODELIGNIFICATION OF COCONUT WOOD SAWDUST USING PLEURATUS SAPIDUS - Wahid Sulaiman; Sugiyarto Sugiyarto; Edwi Mahajoeno (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Coconut wood sawdust is one of the common wastes found in Indonesia and has great potential to be utilized as alternative biomass energy raw materials or cellulose-based biotechnology products. Biodelignification is the process to release cellulose, hemicellulose bond with ligninusing microbes such as fungi, bacteria or enzymes. Pleuratus sapidus one of white rot fungi species who have ability on lignin degradation by produces ligniselulolytic enzymes and proven to be effective and efficient to degrade lignin. The purpose of this study was to determine the optimum incubation time of Pleuratus sapidus between 15, 30, 45 days and the best inoculum concentration between 2.5 ml/ 10 g substrate, 5 ml/ 10 g substrate, 7.5 ml/ 10 g substrate in delignification of coconut wood sawdust. Chesson Data method is used to calculate the lignin, cellulose and hemicellulose in coconut wood sawdust and to detemine percentage of degradation, Data analyzed using SPSS Two Way Anova. Conclusion of the research, the best concentration of inoculum was 5 ml/ 10 gr substrate, with the ability to degrade lignin in coconut wood sawdust as 6.33 % with an optimum incubation time of 45 days.  Keyword : Biodelignfication, Coconut wood sawdust, Ligniselulose, Pleuratus sapidus, White rot fungi.